Scroll:matrices >> find the value 3 row 3 col >> ps (4142)


Written Instructions:

For each Multiple Choice Question (MCQ), four options are given. One of them is the correct answer. Make your choice (1,2,3 or 4). Write your answers in the brackets provided..

For each Short Answer Question(SAQ) and Long Answer Question(LAQ), write your answers in the blanks provided.

Leave your answers in the simplest form or correct to two decimal places.



 

1)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
513
2-25
044
 
,B = 
223
456
165
 
and C= 
15-2
504
3-11
 

(A+B) + C = 




Answer:_______________




2)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
423
3-23
465
 
,B = 
453
557
274
 
and C= 
42-3
402
1-11
 

(A+B) + C = 




Answer:_______________




3)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
524
4-25
145
 
,B = 
253
456
255
 
and C= 
35-2
304
3-13
 

(A+B) + C = 




Answer:_______________




4)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
213
3-26
434
 
,B = 
254
838
156
 
and C= 
25-1
602
1-11
 

(A+B) + C = 




Answer:_______________




5)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
535
2-26
123
 
,B = 
322
547
346
 
and C= 
12-3
503
1-12
 

(A+B) + C = 




Answer:_______________




6)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
325
3-26
152
 
,B = 
434
837
264
 
and C= 
14-3
303
2-13
 

(A+B) + C = 




Answer:_______________




7)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
325
2-23
122
 
,B = 
144
758
476
 
and C= 
33-1
302
3-11
 

(A+B) + C = 




Answer:_______________




8)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
335
4-22
453
 
,B = 
244
646
356
 
and C= 
42-2
705
1-12
 

(A+B) + C = 




Answer:_______________




9)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
312
2-24
433
 
,B = 
132
746
466
 
and C= 
23-3
403
2-13
 

(A+B) + C = 




Answer:_______________




10)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
322
2-25
345
 
,B = 
453
537
244
 
and C= 
43-3
403
3-13
 

(A+B) + C = 




Answer:_______________




 

1)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
513
2-25
044
 
,B = 
223
456
165
 
and C= 
15-2
504
3-11
 

(A+B) + C = 


Answer: 8 Answer: 8 Answer: 4
Answer: 11 Answer: 3 Answer: 15
Answer: 4 Answer: 9 Answer: 10


SOLUTION 1 :
B+C = 
223
456
165
 
+
15-2
504
3-11
= 
371
9510
456
 
 
A+(B+C)=
513
2-25
044
+
371
9510
456
= 
884
11315
4910
 
...(1)
A+B
513
2-25
044
+
223
456
165
= 
736
6311
1109
 
 
(A+B)+C
736
6311
1109
+
15-2
504
3-11
=
884
11315
4910
....(2)

From (1) and (2) we have

A+ (B+C) = (A+B) +C.

(A+B)+C
884
11315
4910


 

 



2)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
423
3-23
465
 
,B = 
453
557
274
 
and C= 
42-3
402
1-11
 

(A+B) + C = 


Answer: 12 Answer: 9 Answer: 3
Answer: 12 Answer: 3 Answer: 12
Answer: 7 Answer: 12 Answer: 10


SOLUTION 1 :
B+C = 
453
557
274
 
+
42-3
402
1-11
= 
870
959
365
 
 
A+(B+C)=
423
3-23
465
+
870
959
365
= 
1293
12312
71210
 
...(1)
A+B
423
3-23
465
+
453
557
274
= 
876
8310
6139
 
 
(A+B)+C
876
8310
6139
+
42-3
402
1-11
=
1293
12312
71210
....(2)

From (1) and (2) we have

A+ (B+C) = (A+B) +C.

(A+B)+C
1293
12312
71210


 

 



3)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
524
4-25
145
 
,B = 
253
456
255
 
and C= 
35-2
304
3-13
 

(A+B) + C = 


Answer: 10 Answer: 12 Answer: 5
Answer: 11 Answer: 3 Answer: 15
Answer: 6 Answer: 8 Answer: 13


SOLUTION 1 :
B+C = 
253
456
255
 
+
35-2
304
3-13
= 
5101
7510
548
 
 
A+(B+C)=
524
4-25
145
+
5101
7510
548
= 
10125
11315
6813
 
...(1)
A+B
524
4-25
145
+
253
456
255
= 
777
8311
3910
 
 
(A+B)+C
777
8311
3910
+
35-2
304
3-13
=
10125
11315
6813
....(2)

From (1) and (2) we have

A+ (B+C) = (A+B) +C.

(A+B)+C
10125
11315
6813


 

 



4)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
213
3-26
434
 
,B = 
254
838
156
 
and C= 
25-1
602
1-11
 

(A+B) + C = 


Answer: 6 Answer: 11 Answer: 6
Answer: 17 Answer: 1 Answer: 16
Answer: 6 Answer: 7 Answer: 11


SOLUTION 1 :
B+C = 
254
838
156
 
+
25-1
602
1-11
= 
4103
14310
247
 
 
A+(B+C)=
213
3-26
434
+
4103
14310
247
= 
6116
17116
6711
 
...(1)
A+B
213
3-26
434
+
254
838
156
= 
467
11114
5810
 
 
(A+B)+C
467
11114
5810
+
25-1
602
1-11
=
6116
17116
6711
....(2)

From (1) and (2) we have

A+ (B+C) = (A+B) +C.

(A+B)+C
6116
17116
6711


 

 



5)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
535
2-26
123
 
,B = 
322
547
346
 
and C= 
12-3
503
1-12
 

(A+B) + C = 


Answer: 9 Answer: 7 Answer: 4
Answer: 12 Answer: 2 Answer: 16
Answer: 5 Answer: 5 Answer: 11


SOLUTION 1 :
B+C = 
322
547
346
 
+
12-3
503
1-12
= 
44-1
10410
438
 
 
A+(B+C)=
535
2-26
123
+
44-1
10410
438
= 
974
12216
5511
 
...(1)
A+B
535
2-26
123
+
322
547
346
= 
857
7213
469
 
 
(A+B)+C
857
7213
469
+
12-3
503
1-12
=
974
12216
5511
....(2)

From (1) and (2) we have

A+ (B+C) = (A+B) +C.

(A+B)+C
974
12216
5511


 

 



6)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
325
3-26
152
 
,B = 
434
837
264
 
and C= 
14-3
303
2-13
 

(A+B) + C = 


Answer: 8 Answer: 9 Answer: 6
Answer: 14 Answer: 1 Answer: 16
Answer: 5 Answer: 10 Answer: 9


SOLUTION 1 :
B+C = 
434
837
264
 
+
14-3
303
2-13
= 
571
11310
457
 
 
A+(B+C)=
325
3-26
152
+
571
11310
457
= 
896
14116
5109
 
...(1)
A+B
325
3-26
152
+
434
837
264
= 
759
11113
3116
 
 
(A+B)+C
759
11113
3116
+
14-3
303
2-13
=
896
14116
5109
....(2)

From (1) and (2) we have

A+ (B+C) = (A+B) +C.

(A+B)+C
896
14116
5109


 

 



7)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
325
2-23
122
 
,B = 
144
758
476
 
and C= 
33-1
302
3-11
 

(A+B) + C = 


Answer: 7 Answer: 9 Answer: 8
Answer: 12 Answer: 3 Answer: 13
Answer: 8 Answer: 8 Answer: 9


SOLUTION 1 :
B+C = 
144
758
476
 
+
33-1
302
3-11
= 
473
10510
767
 
 
A+(B+C)=
325
2-23
122
+
473
10510
767
= 
798
12313
889
 
...(1)
A+B
325
2-23
122
+
144
758
476
= 
469
9311
598
 
 
(A+B)+C
469
9311
598
+
33-1
302
3-11
=
798
12313
889
....(2)

From (1) and (2) we have

A+ (B+C) = (A+B) +C.

(A+B)+C
798
12313
889


 

 



8)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
335
4-22
453
 
,B = 
244
646
356
 
and C= 
42-2
705
1-12
 

(A+B) + C = 


Answer: 9 Answer: 9 Answer: 7
Answer: 17 Answer: 2 Answer: 13
Answer: 8 Answer: 9 Answer: 11


SOLUTION 1 :
B+C = 
244
646
356
 
+
42-2
705
1-12
= 
662
13411
448
 
 
A+(B+C)=
335
4-22
453
+
662
13411
448
= 
997
17213
8911
 
...(1)
A+B
335
4-22
453
+
244
646
356
= 
579
1028
7109
 
 
(A+B)+C
579
1028
7109
+
42-2
705
1-12
=
997
17213
8911
....(2)

From (1) and (2) we have

A+ (B+C) = (A+B) +C.

(A+B)+C
997
17213
8911


 

 



9)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
312
2-24
433
 
,B = 
132
746
466
 
and C= 
23-3
403
2-13
 

(A+B) + C = 


Answer: 6 Answer: 7 Answer: 1
Answer: 13 Answer: 2 Answer: 13
Answer: 10 Answer: 8 Answer: 12


SOLUTION 1 :
B+C = 
132
746
466
 
+
23-3
403
2-13
= 
36-1
1149
659
 
 
A+(B+C)=
312
2-24
433
+
36-1
1149
659
= 
671
13213
10812
 
...(1)
A+B
312
2-24
433
+
132
746
466
= 
444
9210
899
 
 
(A+B)+C
444
9210
899
+
23-3
403
2-13
=
671
13213
10812
....(2)

From (1) and (2) we have

A+ (B+C) = (A+B) +C.

(A+B)+C
671
13213
10812


 

 



10)  

 Verify that A+ (B+C) = (A+B) + C

If A = 
322
2-25
345
 
,B = 
453
537
244
 
and C= 
43-3
403
3-13
 

(A+B) + C = 


Answer: 11 Answer: 10 Answer: 2
Answer: 11 Answer: 1 Answer: 15
Answer: 8 Answer: 7 Answer: 12


SOLUTION 1 :
B+C = 
453
537
244
 
+
43-3
403
3-13
= 
880
9310
537
 
 
A+(B+C)=
322
2-25
345
+
880
9310
537
= 
11102
11115
8712
 
...(1)
A+B
322
2-25
345
+
453
537
244
= 
775
7112
589
 
 
(A+B)+C
775
7112
589
+
43-3
403
3-13
=
11102
11115
8712
....(2)

From (1) and (2) we have

A+ (B+C) = (A+B) +C.

(A+B)+C
11102
11115
8712